2019
DOI: 10.4269/ajtmh.18-0778
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and Cutaneous Leishmaniases in a City in Syria and the Effects of the Syrian Conflict

Abstract: War provides ideal grounds for the outbreak of infectious diseases, and the Syrian war is not an exception to this rule. Following the civil crisis, Syria and refugee camps of neighboring countries witnessed an outbreak of leishmaniasis. We accessed the database of the central leishmaniasis registry in Latakia city and obtained the leishmaniasis data of the period 2008-2016. Our data showed that the years 2013 and 2014 recorded a surge in the number of both cutaneous leishmaniases (CL) and visceral leishmanias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…Observed decreases in number of cases may be attributed to movement out of endemic areas into less-affected parts of the country, into areas with limited access to health services, or into neighboring countries; conversely, observed increase in some governorates could also reflect movements of infected people during the incubation period, as the lesions would appear in the new settlement area and would be reported as local cases. For example, population movements from highly-endemic areas in north-western Syria affected by war (e.g., Aleppo) to safer governorates in the south, northeast, and west may explain shifts in reported number of cases, as recorded in Lattakia [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed decreases in number of cases may be attributed to movement out of endemic areas into less-affected parts of the country, into areas with limited access to health services, or into neighboring countries; conversely, observed increase in some governorates could also reflect movements of infected people during the incubation period, as the lesions would appear in the new settlement area and would be reported as local cases. For example, population movements from highly-endemic areas in north-western Syria affected by war (e.g., Aleppo) to safer governorates in the south, northeast, and west may explain shifts in reported number of cases, as recorded in Lattakia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have noted that the onset of the war coincided with a significant increase in number and distribution of CL cases across the country [10][11][12][13][14][15][16][17][18][19][20][21] and that movements of Syrian refugees led to a general increase in number of CL cases reported from resettlement countries [22][23][24][25][26][27][28][29][30]. Our analysis focuses on a comprehensive quantification of the evolution of CL epidemiology throughout Syria's territory, an exercise that, to our knowledge, has not yet been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is very rare in Syria, and is mainly in the northern provinces where risk is still low. Cutaneous and visceral leishmaniasis, has are endemic in Syria, and their incidence increased in the last years from the internal displacement from the war [ 10 ]. Moreover, diagnosis is mainly made by demonstrating the parasite in stains [ 10 ] which were all normal in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that there was an increase in VL cases in Syria. [ 7 8 ] In our study of VL, the cases originated in north, east, south Tartous due to the randomized population expanding in the last 10 years which increased the contiguity between humans and wild animals which is considered a natural reservoir of leishmaniasis such as dogs and jackals.…”
Section: Discussionmentioning
confidence: 99%